Gastric mucosa as a rare recurrence location of endometrial endometrioid adenocarcinoma - Kathleen Lundeberg; Juliet Wolford; Thomas Reid (Gynecologic Oncology Reports, 2024)
Endometrial cancer is the most common gynecologic malignancy in the United States, with a prevalence of 25.7 per 100,000 women per year (Mahdy et al., 2023). Recurrences of endometrial carcinoma have a mean interval of occurring 2–3 years after primary treatment, with 64 % of cases occurring within 2 years and 87 % by the third year (Kurra et al., 2013). The most common sites of recurrence include the pelvis, pelvic and para-aortic lymph nodes, peritoneum, and the lungs (Kurra et al., 2013). Here, we describe a 72-year-old female with recurrent Stage IIIA endometrial adenocarcinoma in the gastric mucosa, an unusual location for recurrence of this type of cancer.